Quinate-based ligands for irreversible inactivation of the bacterial virulence factor DHQ1 enzyme—A molecular insight† - Rodríguez, Ángela; Maneiro, María; Lence, Emilio; Otero, José M.; van Raaij, Mark J.; Thompson, Paul; Hawkins, Alastair R.; González-Bello, Concepción (Frontiers in Molecular Biosciences, 2023)
Irreversible inhibition of the enzyme type I dehydroquinase (DHQ1), a promising target for anti-virulence drug development, has been explored by enhancing the electrophilicity of specific positions of the ligand towards covalent lysine modification. For ligand design, we made use of the advantages offered by the intrinsic acid-base properties of the amino substituents introduced in the quinate scaffold, namely compounds 6–7 (R configuration at C3), to generate a potential leaving group, as well as the recognition pattern of the enzyme. The reactivity of the C2–C3 bond (Re face) in the scaffold was also explored using compound 8. The results of the present study show that replacement of the C3 hydroxy group of (–)-quinic acid by a hydroxyamino substituent (compound 6) provides a time-dependent irreversible inhibitor, while compound 7, in which the latter functionality was substituted by an amino group, and the introduction of an oxirane ring at C2–C3 bond, compound 8, do not allow covalent modification of the enzyme. These outcomes were supported by resolution of the crystal structures of DHQ1 from Staphylococcus aureus (Sa-DHQ1) and Salmonella typhi (St-DHQ1) chemically modified by 6 at a resolution of 1.65 and 1.90 Å, respectively, and of St-DHQ1 in the complex with 8 (1.55 Å). The combination of these structural studies with extensive molecular dynamics simulation studies allowed us to understand the molecular basis of the type of inhibition observed. This study is a good example of the importance of achieving the correct geometry between the reactive center of the ligand (electrophile) and the enzyme nucleophile (lysine residue) to allow selective covalent modification. The outcomes obtained with the hydroxyamino derivative 6 also open up new possibilities in the design of irreversible inhibitors based on the use of amino substituents.